Financial structure of microenterprise in Colombia (2018)
The study of microenterprise in Colombia is very important. Its contribution to the product, the employment and the distribution of the income, sustains it. The objective of this article is to analyze the financial structure of Colombian microenterprises. The epistemological approach is the empirical-inductive. Research design: non-experimental field. Type of descriptive and transectional study. Technique used: the survey. Instrument: questionnaire applied to owners or directors of 1601 microenterprises located in Bogotá, Medellín, Cali and Barranquilla. Among the results, the financial structure has its own or family savings as a source of financing, followed by banks and financial institutions, supplier and government.